Novel visible-light responsive NCQDs-TiO2/PAA/PES photocatalytic membrane with enhanced antifouling properties and self-cleaning performance. Issue 4 (August 2021) - Heng, Zeng Wei; Chong, Woon Chan; Pang, Yean Ling; Sim, Lan Ching; Koo, Chai Hoon
Abstract: In this study, a novel multifunctional composite membrane with photocatalytic, antifouling and self-cleaning properties were prepared through the surface immobilization of nitrogen doped carbon quantum dots modified TiO2 (NCQDs-TiO2 ) photocatalysts using polyacrylic acid (PAA) as a bridging agent. The surface polymerization of PAA has introduced functional groups for the self-assembly of NCQDs-TiO2 functional layer (denoted as NTO) to improve the hydrophilicity of conventional PES membrane. The modified membranes with varying photocatalyst concentration (0.1, 0.3 and 0.5 wt% NTO) were characterized for their surface chemistry and morphology using SEM-EDX, FTIR, XPS and contact angle analysis. Furthermore, the effect of NCQDs-TiO2 nanocomposite on the membrane performance was assessed in terms of rejection ability, fouling mitigation, self-cleaning and photocatalytic capability using methylene blue as a model pollutant. The characterization results evidenced that the NTO nancomposites were firmly attached on the PES-based supporting layer through the chemical bonding between surface-grafted carboxylic group and Ti atom. The surface hydrophilicity of composite membrane was enormously enhanced following a direct proportionality to NTO loading. The novel NTO/PAA/PES membrane also demonstrated high resistance to MB fouling and was able to revive 93.7% of original water fluxes upon 15 min of visible-light irradiation. Moreover, the modified membranes could efficiently retain 90.9% of MB dye pollutant. The outstanding antifouling and self-cleaning performance were reasonably attributed to the intrinsic hydrophilicity and robust photocatalytic activity of NTO layer. This was further confirmed by the photodegradation of MB wherein the NTO-0.5/PAA/PES membrane degraded 94.9% of MB under 1 hr of visible-light irradiation. With its twofold advantages of membrane filtration and photocatalysis, the visible-light responsive photocatalytic membrane demonstrates huge potential in waste water treatment which could minimize membrane fouling and increase reusability of photocatalyst. Graphical Abstract: ga1 Highlights: Synthesis of nitrogen doped carbon quantum dot/titanium dioxide deposited membrane. Fabrication of photocatalytic membrane via UV-induced graft polymerisation method. Excellent antifouling behaviour due to enhanced surface hydrophilicity. Effective photocatalytic and self-cleaning ability under visible-light irradiation.